Thymoquinone and cancer treatment: A scientometric analysis (Bangladesh Journal of Medical Science, 2026)
Background Thymoquinone (TQ), a bioactive compound derived from Nigella sativa, has gained attention for its multifaceted therapeutic potential, particularly its significant anticancer properties. Objective This study aimed to conduct a comprehensive bibliometric analysis to evaluate the global research landscape on TQ’s impact on neoplasms. Methods A bibliometric analysis was performed using data from the Web of Science Core Collection and Scopus databases, covering the years 1997–2024. A total of 896 studies authored by 3695 researchers and published across 485 sources were included in the analysis. The study assessed publication trends, key contributors, institutional productivity, and thematic areas of focus. Results The scholarly output on TQ and cancer exhibited an annual growth rate of 14.53%, peaking in 2021. The journal Molecules was the most prolific in terms of publication count, whereas Cancer Research garnered the highest local citations. Leading institutions such as the Egyptian Knowledge Bank and King Abdulaziz University were identified as major contributors. Collaborative research comprised nearly 20% of the total output. Mechanistically, TQ was shown to exert anticancer effects by inhibiting cell proliferation, inducing apoptosis, and disrupting key processes such as migration, invasion, and epigenetic modifications. Importantly, TQ demonstrated a non-toxic profile in normal cells, underscoring its potential for combination therapies. Conclusion This bibliometric analysis provides valuable insights into global collaboration networks, influential researchers and institutions, and evolving thematic trends in TQ-related cancer research. The findings establish a foundation for future studies aimed at optimizing and expanding the therapeutic applications of TQ in oncology.BJMS, Vol. 25 No. 02 April’26 Page: 507-517